(3GdYbO GdaQjO aj Yde GdJLhjOs - (3eMeO Hf eMehO Hf eMeO Hf CMeO, TeS GdOjf GdSeQbfOj,J (B780 (3g` s ((3eSde Hf CMeO s)
(3ChdgG (B:s
(3HMeO Gddg CfRd GdPcQ ddhQj jchf EHJOGj aj GdCehQ hGdEfJgG hCfTj UdGI Ke CfTj SdGeI Ydi NjQ Ndb Gddg deSg Ydi GdeOi s
(3BNQgG (B:s
(3eMeO GdoeNJGQ hef fSd gGTe hCaVd ef ahb GdHSjWI bO eTi hBd hCUMGH hCJHGYg hef CLGO jYde ddbQGAg hGdGOG JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3efXheI ai GdJLhjOs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B4s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1152s
Keywords: (3GdbQGAGJ hGdJLhjOs